Cr+6 Controlled Nucleation in SiO2-MgO-Al2O3-K2O-B2O3-F Glass Sealant (SOFC) - Garai, Mrinmoy; Karmakar, Basudeb; Roy, Shibayan (Frontiers in Materials, 2020)
This study highlights the strong effect of chromium (Cr6+) as nucleating agent in SiO2-MgO-Al2O3-B2O3-K2O-F glass sealant. Al2O3 of the glass was gradually substituted by K2Cr2O7 content that considerably tuned the crystallization, microstructure, thermal and mechanical properties. The distinctive feature of this study is the induction of nucleation and crystallization in glass matrix on addition of Cr6+ content without performing any heat-treatment. The melt-quenched SiO2-MgO-Al2O3-B2O3-K2O-F glass with zero Cr6+ content is amorphous, which in presence of Cr6+ content became crystalline with MgCr2O4, K3CrF6, MgF2 and mullite (3Al2O3.2SiO2) phases. Glassy features in DSC and dilatometric thermal properties (Tg, Td, thermal expansion) was attained in glass without Cr- content, but glass-ceramic like features obtained for Cr- containing glasses. For those glasses large thermal expansion (>11 ×10-6/K at 50-800°C) was ascribed, that is compatible with solid oxide fuel cell (SOFC) components (electrode, interconnect etc) during operating temperature ~800°C. From FESEM study, dense microstructure morphology sorted with 200-500 nm sized crystallites is obtained in 2 mol% K2Cr2O7 containing glass. In higher Cr- containing glasses, the microstructure becomes more compact with 10-50 µm sized plate like crystals. Higher crystallinity thus ascertained for higher Cr- containing glasses, and this directly corresponds to density and mechanical properties. From nanoindentation test, the hardness and elastic modulus were estimated as 0.6 (±0.5) and 25 (±10) GPa, respectively for base glass and that increased to 3.3-8.4 and 58-94 GPa, respectively for Cr- containing glasses. Microhardness of the base glass is estimated 3.63 (±0.18) GPa which increased to 3.94-6.08 GPa in Cr- containing glasses. The typical microstructure, compatible thermal and mechanical properties make 2 mol% K2Cr2O7 doped SiO2-MgO-Al2O3-B2O3-K2O-F glasses suitable for high temperature sealing application like SOFC.